A fountain as the “first thing” in the urban genetics - Kapustin, Petr (project baikal, 2021)
Often placed in the heart of old cities, the fountain has not become a focus of architectural problematics, being pushed aside by more monumental and significant constructions and large-scale issues. When identifying the origins of the city, or its source, one usually thinks of something harder than water and more pragmatic than fine streams. However, the sources are of special magic, which, as claimed by Vitruvius, traces its origin to the Egyptians, and from which all cities take their origin. The article makes an attempt to study the phenomenon of fountains and to comprehend its scope.